2005
DOI: 10.1203/01.pdr.0000180568.97221.56
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphy Correctly Predicts Sleep Behavior in Infants Who Are Younger than Six Months, When Compared with Polysomnography

Abstract: Actigraphy has been widely used in adults and children. In infants, validation of actigraphy has typically used a comparison with behaviorally determined sleep state classification rather than polysomnography (PSG). This study validated actigraphy against PSG for determining sleep and waking states in infants who were younger than 6 mo. Twenty-two healthy infants, 13 term and 9 preterm, were studied at three different matched postconceptional ages. Actigraph data were compared with PSG recordings in 1-min epoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 10 publications
6
115
4
Order By: Relevance
“…By comparing sensitivity and specificity, the performance of our classifier is in the same range as that obtained by So et al (2005). However, their database contained very few wake epochs (<10%).…”
Section: Discussionmentioning
confidence: 53%
“…By comparing sensitivity and specificity, the performance of our classifier is in the same range as that obtained by So et al (2005). However, their database contained very few wake epochs (<10%).…”
Section: Discussionmentioning
confidence: 53%
“…Sitnick et al 19 showed that an algorithm commonly used with adults is too sensitive with a population of young children, resulting in high false negative rates (i.e., actigraphy detects wakefulness when the child is probably sleeping). In fact, although several studies with infants and children have reported that various actigraphy devices are highly correlated (> 80%) with PSG or videosomnography, 14,[16][17][18][19][20][21][22][23] most of these studies have shown very low ability to correctly identify wakefulness 14,17,19,22 and hence, sleep fragmentation. 24 Nevertheless, the American Academy of Sleep Medicine (AASM) states that the use of actigraphy in normal children and special pediatric populations is indicated for the assessment of sleep patterns and response to treatment.…”
mentioning
confidence: 99%
“…Under this nocturnal environment, the infant's sleep measures were assessed objectively. Because the sleep measures retrieved from actigraph were highly correlated with polysomnography and observation method [18,19], it was confirmed that waking time and waking duration during night was decreased and the longest sleep duration was increased. Thus, the sleep measures of infants assessed by actigraph showed significant developmental change in this study.…”
Section: Infant's Sleepmentioning
confidence: 87%
“…This device is well suited for long-term observation of sleep conditions. It is also considered to be a reliable data collection method of sleep in young children [19]. Mothers of infants were asked to keep the actigraph on their infant's ankles for a week.…”
Section: The Infant's Sleepmentioning
confidence: 99%